Effect of deep cryogenic treatment on cyclic fatigue resistance of controlled memory wire nickel-titanium rotary instruments - Yazdan Sabet; Samira Shahsiah; Mohammad Yazdizadeh; Sana Baghamorady; Mansour Jafarzadeh (Wolters Kluwer Medknow Publications, 2020)
Background: Cryogenic methods have been used to increase the wear, abrasion, corrosion resistance and to improve the strength of metals. The aim of this study was to evaluate the effect of cryogenic treatment on the cyclic fatigue resistance of rotary nickel-titanium (NiTi) instruments. Materials and Methods: In this in vitro study, 20 Hyflex (Coltene, Altstätten, Switzerland) nickel-titanium instruments, size 25, 0.06 taper, were randomly divided into two groups as follows: untreated NiTi rotary files (Group A) and cryotreated NiTi rotary files (Group B). The instruments of Group A were completely immersed in a cryocan containing liquid nitrogen (-196°C) for 24 h. After 24 h, the instruments were removed from the bath and were allowed to return to room temperature gradually. All files were used (at a speed of 500 rpm and a torque of 2.5 Ncm) in an artificial canal with a 60° curvature until fracture. Time to failure was recorded with a stopwatch in seconds and subsequently converted to number of cycles to fracture (NCF). Groups were compared using the independent-samples t-test. The level of statistical significance was set at 0.05. Results: Mean NFCs in Group A and B were 1576 and 1395, respectively. However, statistical analysis showed that there was no significant difference between the groups (P = 0.2). Conclusion: Deep cryotherapy of NiTi endodontic files cannot improve the cyclic fatigue resistance of HyFlex files, but further studies are required to evaluate these cryogenically treated NiTi files clinically.